2018
DOI: 10.1115/1.4040383
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Surface Patterning on the Thermal Properties of Textured Thrust Bearings

Abstract: Contact performance can be enhanced by using textured surfaces. These are also found to have influences on lubricated contacts. A procedure to find the optimal partially textured thrust bearing configuration is presented in this study. A parallel sector-pad thrust bearing is simulated by a three-dimensional (3D) computational fluid dynamics (CFD) model. The stationary surface of the bearing is textured with dimples, while the rotor surface is flat. The results of the baseline model are validated by experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…where r v and h v are the reference values in the radial direction and of the film thickness, respectively. Hence, by substituting equation (12) into equation ( 8) and using the dimensionless form of equation ( 6), the following is obtained:…”
Section: Analytical Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…where r v and h v are the reference values in the radial direction and of the film thickness, respectively. Hence, by substituting equation (12) into equation ( 8) and using the dimensionless form of equation ( 6), the following is obtained:…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…Studies have shown that an optimal dimple depth, texture fraction, and the number of pads can maximize the load-carrying capacity. 1114 Numerous fluid-dynamical models have been established to improve the load-carrying capacity by optimizing the geometrical parameters and distribution of the dimples. 15,16…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various texturing techniques were employed in recent studies including etching techniques, photoetching, machining, ion beam texturing, and laser texturing. 13 The surface texturing which could be divided into full texturing and partial texturing was an encouraging approach to improve the tribological properties, 14,15 and. It is interesting that partial texturing provided a higher load-carrying capacity and lower friction power loss than full texturing, [16][17][18] which was furtherly verified by theoretical analysis or experimental verification in textured engine cylinder, piston rings, and mechanical seals.…”
Section: Introductionmentioning
confidence: 99%
“…The development of air foil journal bearings has been relatively mature [8][9][10]. Later, researchers began to devote themselves to the research of air thrust foil bearings [11][12][13][14][15][16][17][18]. In 1983, Heshmat H. and Walowit J.…”
Section: Introductionmentioning
confidence: 99%